Isotopic Abundances in Presolar SiC Grains accounted by s-Processing from MHD-induced Mixing in low mass AGB stars. (October 2020) - Palmerini, S.; Busso, M.; Vescovi, D.
Abstract: In the past, the observational evidence that s-process elements from Sr to Pb are produced by stars ascending the so-called Asymptotic Giant Branch (or AGB) could not be explained by self-consistent models, forcing researchers to extensive parameterisations. The crucial point is to understand how protons can be injected from the envelope into the He-rich layers, yielding to the formation of 13 C and then the activation of the 13 C(α, n) 16 O reaction. In the last decade, some physically-based mixing mechanisms have been considered to solve this problem. Nowadays, a big step forward in s-process studies would be to understand what is among the suggested ones the physical model better accounts for the observational constrains. In this paper we analyse a model where the 13 C forms as a feedback of MHD processes in the stellar plasma. We compare results of nucleosynthesis models for low mass AGB stars (M<3M©), developed from the MHD scenario, with the record of isotopic abundance ratios of s-elements in presolar SiC grains, which were shown to offer precise constraints on the 13 C reservoir. We find that n-captures driven by magnetically-induced mixing can well account for the SiC data and that this is due to the fact that our 13 C distribution fullfills the above constraints rather accurately. We show comparisons between model predictions and measurements for isotopes of Sr, Zr, Ba, Mo and Ru as representative examples of light and heavy s-elements.